Wafer-size growth of 2D layered SnSe films for UV-Visible-NIR photodetector arrays with high responsitivity. Issue 13 (24th March 2020) - Hao, Lanzhong; Du, Yongjun; Wang, Zegao; Wu, Yupeng; Xu, Hanyang; Dong, Shichang; Liu, Hui; Liu, Yunjie; Xue, Qingzhong; Han, Zhide; Yan, Keyou; Dong, Mingdong
Abstract : Wafer-size SnSe thin films with high uniformity and high crystal quality were grown by magnetron sputtering technique, and exhibit a highly sensitive to a broadband wavelength with high responsivity of 277.3 AW −1 and detectivity of 7.6 × 1011 Jones. Abstract : Due to its excellent electrical and optical properties, tin selenide (SnSe), a typical candidate of two-dimensional (2D) semiconductors, has attracted great attention in the field of novel optoelectronics. However, the large-area growth of high-quality SnSe films still remains a great challenge, which limits their practical applications. Here, wafer-size SnSe ultrathin films with high uniformity and crystallization were deposited via a scalable magnetron sputtering method. The results showed that the SnSe photodetector was highly sensitive to a broad range of wavelengths in the UV-visible-NIR range, especially showing an extremely high responsivity of 277.3 A W −1 with the corresponding external quantum efficiency of 8.5 × 10 4 % and detectivity of 7.6 × 10 11 Jones. These figures of merits are among the best performances for the sputter-fabricated 2D photodetector devices. The photodetecting mechanisms based on a photogating effect induced by the trapping effect of localized defects are discussed in detail. The results indicate that the few-layered SnSe films obtained from sputtering growth have great potential in the design of high-performance photodetector arrays.